Historical analysis of sus financing criteria in the field of primary health care: an integrative review (Research, Society and Development, 2022)
The present work focuses on the historical analysis of SUS funding criteria in the scope of Primary Health Care (PHC), discussing changes in the implementation of PNAB/2011, regulated by Ordinance 2.488/2011 through its readjustment in 2017 (Ordinance 2.436/2017). In this perspective, we find several difficulties on the theme, from the lack of knowledge of the importance of PHC funding by the manager and health professionals, to the lack of accessible means, implementation techniques, material and human inputs to achieve targets imposed by the regulated indicators through the funding criteria. In view of this, the research aims to explain changes that occurred in the criteria of financing of PHC, with focus on the main regulatory instruments, being: the PNAB/2011 and its review carried out in 2017, instituting in 2019, the Previne Brasil. This research is important, because it allows to identify changes in the model of monitoring and evaluation of the strategic actions that should be offered by the health teams, corroborating for the promotion and dissemination of information that is indispensable for the effective management in health. It is a literature review, with a qualitative and dialectical approach, in order to propose a diagnostic research. In the light of the above, it is concluded that the implementation of the financing model of PAS, based on the PMAQ and Previne Brasil criteria, has not yet achieved effective methods to meet the needs indicated by the structuring of PAS. The creation of the PNAB brought, regulations that implemented the new financing model of the PHC, but does not fully guarantee the transfers destined to the full coverage of health services.